Dopplerometry of fetoplancentral blood flow in the dynamics of pregnancy in women with treated infertility caused by hyperprolactinemia syndrome of tumocular and non-tumocular genesis - O. Nosenko; O. Martynovska (Journal of Education, Health and Sport)
The aim of the study was to study the state of blood circulation in the fetoplacental system in the dynamics of gestation using Dopplerometry in women with cured infertility due to hyperprolactinemia syndrome of tumor and non-tumor genesis. Material and methods. 57 pregnant women with cured infertility due to hyperprolactinemia syndrome (21 women with pituitary microprolactinomas and 36 patients with idiopathic hyperprolactinemia), 30 relatively healthy pregnant women of the control group without neuroendocrine disorders were under observation. Doppler study of the pulsatile index (PI) of blood flow in the uterine arteries at 11-12, 29-31 and 36-37 weeks, PI of the umbilical artery, middle cerebral artery and ductus venosus at 29-31 and 36-37 weeks was performed. Cerebroplacental ratio was assessed to assess the distribution of blood flow between the brain and the placenta of the fetus. Results. The average PI of the uterine arteries was the highest at 11-12 weeks of gestation and throughout pregnancy exceeded the similar indicator in pregnant women without neuroendocrine disorders, but was not statistically different in individuals with hyperprolactinemia of tumor and non-tumor genesis. The average PI of the umbilical artery exceeded the similar indicator in healthy pregnant women in the second and third trimesters, and at 36-37 weeks it was significantly higher in women with microprolactinomas compared with individuals with idiopathic hyperprolactinemia. The average PI of the middle cerebral arteries in the second and third trimesters was lower than that in pregnant women without neuroendocrine disorders, but there were no significant statistical differences between pregnant women with hyperprolactinemia of tumor and non-tumor genesis. Cerebroplacental ratio was reduced in individuals with hyperprolactinemia of tumor and non-tumor genesis compared to pregnant women without neuroendocrine disorders, while among pregnant women with hyperprolactinemia in the cohort of individuals with microadenomas this indicator was lower than in pregnant women without neuroendocrine disorders. No differences were found in the average PI of the ductus venosus in pregnant women with hyperprolactinemia and pregnant women without neuroendocrine disorders. Conclusions. Pregnancy in women with cured infertility due to hyperprolactinemia syndrome of tumor and non-tumor genesis is characterized by abnormal changes in blood circulation in the fetoplacental system in the dynamics of gestation, which indicate the presence of fetoplacental dysfunction of varying degrees of severity in such women and the need for appropriate therapeutic and preventive measures during pregnancy.